Tributaries and deltas: efficient and robust aggregation in sensor network streams - Manjhi, Amit; Nath, Suman; Gibbons, Phillip B. (SIGMOD '05: Proceedings of the 2005 ACM SIGMOD international conference on Management of data, 2005)
Existing energy-efficient approaches to in-network aggregation in sensor networks can be classified into two categories, tree-based and multi-path-based, with each having unique strengths and weaknesses. In this paper, we introduce Tributary-Delta, a novel approach that combines the advantages of the tree and multi-path approaches by running them simultaneously in different regions of the network. We present schemes for adjusting the regions in response to changes in network conditions, and show how many useful aggregates can be readily computed within this new framework. We then show how a difficult aggregate for this context—finding frequent items—can be efficiently computed within the framework. To this end, we devise the first algorithm for frequent items (and for quantiles) that provably minimizes the worst case total communication for non-regular trees. In addition, we give a multi-path algorithm for frequent items that is considerably more accurate than previous approaches. These algorithms form the basis for our efficient Tributary-Delta frequent items algorithm. Through extensive simulation with real-world and synthetic data, we show the significant advantages of our techniques. For example, in computing Count under realistic loss rates, our techniques reduce answer error by up to a factor of 3 compared to any previous technique.